Homogeneously Emitting, Mechanically Stable, and Efficient fs‐Laser‐Machined Fiber Diffusers for Medical Applications. Issue 4 (8th December 2020) - Ströbl, Stephan; Wäger, Felix; Domke, Matthias; Rühm, Adrian; Sroka, Ronald
Abstract : Background and Objectives: Light delivery is an essential part of therapy forms like photodynamic therapy (PDT), laser‐induced thermotherapy, and endovenous laser therapy. While there are approaches to the light application for all three therapies, there is no diffuser that can be used for all three approaches. This diffuser must meet the following criteria: Homogeneous radiation profile over a length of 40 mm, efficient light extraction in the diffuser area, mechanical breakage resistance as well as thermal stability when applying high power. Study Design/Materials and Methods: An ultrashort pulse laser was used to inscribe inhomogeneities into the core of a fused‐silica fiber core while scanning the laser focus within a linear arrangement of cuboids centered around the fiber axis. The manufactured diffuser was optically and mechanically characterized and examined to determine the maximum power that can be applied in a tissue environment. Results: Based on the analysis of all examined diffusers, the manufactured diffuser exhibits an emission efficiency ε = (81.5 ± 5.9)%, an intensity variability of (19 ± 5)% between distal and proximal diffuser end, and a minimum bending radius R b = (15.4 ± 1.5) mm. It was taken advantage of the fact that the outer areas of the fiber core do not undergo any structural changes due to the machining and therefore do not suffer a major loss of stability. Tissue experiments revealed that a maximal power of 15 W was deliverable from the diffuser without harming the diffuser itself. Conclusions: It could be shown that a diffuser manufactured by ultrafast‐laser processing can be used for low power applications as well as for high power applications. Further tests have to show whether the mechanical stability is still maintained after the application of high power in a tissue environment. Lasers Surg. Med. © 2020 Wiley Periodicals LLC